Pengaruh larutan patirasa setempat Lidokain hidroklorida terhadap serabut saraf perifer tikus dan regenerasinya=The Effects of Local HCl Anesthetic Solution on Pberipheral Nerve Fibers and Its Regeneration - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT A histological study of the effect of local anesthetic solution ofIICI lidew-nine on the myelin and axon of the sciatic nerve has been done in order to know the possibility of the occurence of the toxic effects of this anesthetic on the axon and myelin and its regeneration. In this study, 64 male Wistar rats weighed Â± 250 grams were used. The anesthetic solution used were 2 persen, 5 persen and 7 persen HCl lidocaine. Rats were injected into the inflamed and non-inflamed tissues. For the examination of the axons, a paraffin method of tissue preparations with Bodian staining was done, and for the myelin, a frozen section and Sudan Black staining were used. The observations were done under the light microscope with 400x magnification, whereas the myelin and axonal counts were done using the Rasmussen & Herrick method. Three ways analysis of variance and student's 1-test were used to analyze the result of this study. The results ofthis study showed that there were myelin and axonal degenerations after 5 persen and 7 persen HCI lidocaine injection in the non-inflamed tissues. However, no myelin and axonal damages were found after 2 persen HCI lidocaine injection in the non- inflamed tissues. Myelin and axonal degenerations after 5 persen and 7 persen HCI lidocaine injection in the inflamed tissues were more severe than those in the non-inflamed tissues. Myelin and axonal regenerations caused by 2 persen, 5 persen and 7 persen HCI lidocaine injections in non-inflamed tissues occurred on the 30th day, whereas in the inflamed tissues injected with 5 persen and 7 persen HCI lidocaine anesthetic myelin and axonal regenerations had not been seen on the 30th day.